Wheat plant response to zinc enrichment: results from a big plot assay - Rodrigo, Sara; J. Lidon, Fernando; H. Reboredo, Fernando; Silva, M. Manuela; Simões, María M.; Costa, A. Rita (Emirates Journal of Food and Agriculture, 2023)
One third of the global population suffers Zn deficiency, which directly affects their health and the health-bill of all world countries. In this study, the application of Zn sulphate at the latest developing stages (anthesis and milk-dough stages) of bread wheat in Mediterranean conditions were tested for grain and leaves enrichment capacity and antioxidant activities prompting. Variety effects were found to be significant to success in enriching leaves and grains with Zn. While Almansor and Roxo varieties increased more than 50% and close to 40% respectively their amount in grain Zn, no significant differences were found for Paiva variety with or without Zn treatment. Regarding the leaves, Zn amount increases of 110, 230 and 300 ppm of Zn were figured out in Almansor, Roxo and Paiva varieties respectively. Antioxidant compounds in leaves showed to be higher when zinc treatment was applied in Almansor variety. Quality traits of the grain wheat were barely affected by the increase of the Zn amount; Roxo variety grains increased the protein and the dry gluten concentration, while Almansor grains were heavier and Almansor flour showed higher tenacity. It can be concluded that Zn enrichment in wheat plants caused variation in both grain and leaves mineral profile, and antioxidants in leaves. Keywords: Antioxidants, Rainfed conditions, RXF, Winter cereals, Zinc